Catch per unit effort of coastal prawn trammel net fishery in Izmir Bay, Aegean Sea - AKYOL, O.; CEYHAN, T. (Mediterranean Marine Science, 2009)
Catch per unit effort (CPUE) data from the coastal trammel prawn net fishery was estimated from fishery-dependent surveys in Izmir Bay (Aegean Sea) during the 2004-2005 fishing season. Catches were sampled from 18 boats for a total of 170 landings, 60 landings from April to July (first period) and 110 landings from August to November (second period). The mean CPUEs were 2.56 ± 0.39 kg. 10 net unit-1 in the first period and 2.29 ± 0.20 kg. 10 net unit-1 in the second period, and not significantly different between periods (P>0.05).